(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In the article in Scientific achievements of the famous Ukrainian scientist-economist G. F are being illuminated. Symonenko Tune with the institutional economic theory. The contribution to enlargement and deepening of knowledge on this direction of economic science is Shown, in particular about action of economic laws in material and intangible production. The development of the scientific program of the further socio-economic development of Ukraine envisages studying the theoretical developments of scientists of economic science, which could be used to develop their own, national model of economic reform in Market basis. Our Domestic science has a whole tribe of prominent economists, who, despite different adverse circumstances, primarily lack of statehood, Fruitfully Worked on the scientific field. Among them-professor of Kyiv Imperial University of St. Vladimir G. F. Simonenko. His scientific works positive affected the development of economic science, in particular, its direction as institutional economic theory. The Study of scientific heritage of G. F. Symonenko will reduce the number of little-known scientists, will open (resurrect) new names in science. Native scientists from his scientific creativity will draw Enthusiasm, inspiration for his fruitful work, certain ideas for further creative development of economic theory. Purpose of article There is a study of creative achievements of the well-known Ukrainian scientist-economist G. F. Symonenko, where questions are violated with the institutional economic theory or tangent to it. In the process of research increased attention to the disclosure of such tasks as: The attitude of G. F. Symonenko to material and intangible productions, their interrelation and conditions of existence; Reflections on the action of economic laws; Interpretation of the category of productive and unproductive work; Difference of theory of classical political economy from the teaching of old-historical economic school; Studying the ratio of individual and public welfare; Detail of analytical observation of economic phenomena and facts in different historical circumstances; Deepening of observation methodology and abstraction in economic research. In the writings of G. F. Symonenko, the material and non-material production was investigated, the action of economic laws was studied, especially in creation of services and goods. By Changing the conditions of economic laws ’ action, the State can influence economic relations and welfare of people. The natural nature of the laws, their manifestations in the process of economic activity of people is Underlined. The productive and unproductive work in the spirit of the requirements of institutional economic theory, their harmonious correlation is Considered. People’s welfare in close connection with the political and moral conditions is being covered. The ratio of individual and public well-being was Studied. In Depth methodology of economic research, it is indicated on equality and equal value of all methods of studying economic phenomena and processes. Methodological vision of the necessity of consideration of economic activity in the position of morality is Substantiated.